Recent Advances of Acute Kidney Injury in Hematopoietic Cell Transplantation - Miyata, Masahiro; Ichikawa, Kazunobu; Matsuki, Eri; Watanabe, Masafumi; Peltier, Daniel; Toubai, Tomomi (Frontiers in Immunology, 2022)
Acute kidney injury (AKI) is a common complication of allogeneic hematopoietic cell transplantation (allo-HCT) and is associated with non-relapse mortality (NRM) and quality of life (QOL). Various factors include nephrotoxic drugs, infectious diseases, thrombotic microangiopathy (TMA), and sinusoidal obstruction syndrome (SOS) mediate AKI. However, it can be difficult to identify the cause in each patient. On the other hand, acute graft-versus-host disease (aGVHD), which is a major complication of allo-HCT, is mainly targeted on the intestine, liver, and skin but renal lesions are not clear. Severe aGVHD is known to be a risk factor for AKI, suggesting a link between the two. Studies using animal models reported infiltration of donor-derived cells into glomeruli and renal tubules and increased expression of inflammatory cytokines in the kidney after allo-HCT. It has been pointed out that the kidney may be a target of aGVHD. Herein, we describe the pathophysiology of renal injury after allo-HCT, focusing on GVHD.